2022
DOI: 10.7717/peerj-cs.951
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning methods for inverse problems

Abstract: In this paper we investigate a variety of deep learning strategies for solving inverse problems. We classify existing deep learning solutions for inverse problems into three categories of Direct Mapping, Data Consistency Optimizer, and Deep Regularizer. We choose a sample of each inverse problem type, so as to compare the robustness of the three categories, and report a statistical analysis of their differences. We perform extensive experiments on the classic problem of linear regression and three well-known i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…In recent years, deep learning has made significant advancements, particularly in fields like image recognition and natural language processing ( Fujiyoshi, Hirakawa & Yamashita, 2019 ; Kamyab et al, 2022 ). For instance, convolutional neural networks (CNNs) have made breakthroughs in the application of image recognition ( Rawat & Wang, 2017 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In recent years, deep learning has made significant advancements, particularly in fields like image recognition and natural language processing ( Fujiyoshi, Hirakawa & Yamashita, 2019 ; Kamyab et al, 2022 ). For instance, convolutional neural networks (CNNs) have made breakthroughs in the application of image recognition ( Rawat & Wang, 2017 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Fig. 3, we show the distribution of errors on the mesh D tr (16) for the training dataset. Here every point is colored according to the largest of all errors (15) for the 3 concentrations.…”
Section: Data Generationmentioning
confidence: 99%
“…An example of an inverse problem -the determination of parameters for the reaction-diffusion equation -is given in [22]. A review of neural networks for solving linear inverse problems is given in [16].…”
Section: Introductionmentioning
confidence: 99%
“…Hybrid inverse modeling algorithms combining traditional approaches with machine learning techniques are promising to improve inverse modeling results. A review of the applications of machine learning methods to inverse problems can be found in [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%